Desarrollo y aplicación de Xerogeles de carbono en el tratamiento de efluentes acuosos - Mar Ortiz , Alondra Fabiola; Salazar Rábago , Jacob Josafat; Loredo Cancino , Margarita; Sánchez Polo, Manuel; Cerino Córdova, Felipe de Jesus (Quimica Hoy, 2019)
Carbon xerogels are materials with an easy synthesis, to which various modifications can be made to their textural and optical properties. Likewise, these materials have been widely used in various areas of science such as catalysis, adsorption processes, photocatalysis and electrochemistry; The use of these materials in wastewater treatment processes will be addressed due to their excellent behavior in the removal of contaminants.